"אני את המלחמה כבר הבאתי הביתה": במלחמה שם בחוץ והמלחמה כאן בפנים ברומן ורד הלבנון מאת לאה איני - לוי חזן, יעל (מכאן, 2016)
The essay opens with a theoretical discussion of two central underlying themes in Aini’s novel: the dual war of women and women’s autobiographical writing. XV The review of the dual war of women points to the connections between militarism and military violence and domestic violence, sexual abuse, and incest. The review of women’s autobiographical writing shows how, while men’s autobiographical writing is considered to have representative value because it supposedly expresses the social, cultural, and national experience, beyond the personal life of the protagonist, women’s autobiographical writing is considered private and specific, and therefore is not considered representative literature. This is not only because of the focus of women’s autobiography on the domestic sphere, but also because of the split in emotions and identity that is part of women’s political, social, and psychological experience due to their exclusion from the public sphere and relegation to the private sphere. The essay emphasizes how Aini’s novel expresses strong criticism by undermining the conventions of the genre of autobiography while testing and pushing the boundaries between truth and fiction, self and other, one and many. In addition, the novel challenges the archetype of the nurse and criticizes the military establishment, the security discourse, and the language of war.